Teachers’ Strategies in Teaching English after Pandemic Era at SMA Negeri 12 Makassar - Wa Ima Asnan; Suharti Siardjuddin; Hasnani (CV. Eureka Murakabi Abadi, 2023)
This study aimed to find out how the teachers’ strategies in teaching English after the pandemic at SMA Negeri 12 Makassar. This study used a qualitative method. The sample in this study was two teachers, the data collection techniques in this study used observation, interviews and documentation. In collecting data, researchers used observations and interviews with English teachers at SMA Negeri 12 Makassar. Based on the research of the first teacher’s research, used metacognitive strategies to evaluate students’ learning outcomes. The evaluation carried out was in the form of giving assignments and working on practice questions and making preparation of learning plans in the teaching and learning process. While, the second teacher uses memory strategy to review teaching. The review carried out was in the form of material repetition and metacognitive to complete learning plans. The conclusion of this study was that the teacher one only used one strategy, namely metacognitive strategy and the teacher two used two strategies, namely metacognitive strategy and memory strategy. The strategy used by the two teachers can help the teaching and learning process, especially in the post-pandemic era.